2017
DOI: 10.1080/02614367.2017.1310283
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of self-selected leisure activities, trait coping and their relationships with sleep quality and depressive symptoms

Abstract: (2017) Dimensions of self-selected leisure activities, trait coping and their relationships with sleep quality and depressive symptoms, Leisure Studies, 36:6, 838-851,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Control of leisure time predicted fewer awakenings. Recent research (Merritt et al 2017) found selfselected leisure activities to improve sleep quality. Moreover, the current study is the first to test not only work conditions but also private stressors and control during leisure time to predict sleep quality (as was continuously assessed by objective and subjective sleep indicators across a working week).…”
Section: Discussionmentioning
confidence: 99%
“…Control of leisure time predicted fewer awakenings. Recent research (Merritt et al 2017) found selfselected leisure activities to improve sleep quality. Moreover, the current study is the first to test not only work conditions but also private stressors and control during leisure time to predict sleep quality (as was continuously assessed by objective and subjective sleep indicators across a working week).…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, we did not find any significant moderator effects for trait PCs in the role of condition in BP or negative affect responses. PCs is a complex and young concept with studies assessing it in several different ways (Merritt et al, ; Williams et al, ; Zawadzki et al, ). As measurement for this trait is increasingly being developed and refined, future studies may utilize alternative surveys to tap into this measure, such as the Thought Control Questionnaire, Thought Occurrence Questionnaire, and the White Bear suppression inventory (Zawadzki et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Two scales were used to measure PCs in order to avoid relying on a single scale that can be strongly related to another diagnosis such as depression or anxiety (Merritt et al, ). First, trait rumination was assessed with the 22‐item Ruminative Response Scale (Nolen‐Hoeksema & Morrow, ) that measures brooding, reflective, and depressive coping responses to negative events (e.g., “think about a recent situation, wishing it had gone better”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Williams et al, 2016). For instance, Merritt, Zawadzki, Di Paolo, Johnson, and Ayazi (2017) found among young adults that more distraction associated with self-selected leisure activities (i.e., preferred activities like jogging or prayer done to escape from daily stress and/or to keep daily routine) is linked with less depressive symptoms and better subjective sleep quality at higher levels of JHAC. Thus, as prayer could represent an SSLA, perhaps a more tailored intervention for the high JHAC and low education risk group is required.…”
Section: Discussionmentioning
confidence: 99%